THE INFLUENCE OF LEARNING MODEL TAKE AND GIVE ON THE STUDENT STUDY RESULT OF LEARNING MATERIAL COOLING SYSTEM IN GRADE XI LIGHT VEHICLE ENGINEERING AT SMKN 1 PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Abrari Sauqi; Vontas Alfenny Nahan (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
One of several factors of low quality in the teaching of material to explain the components of cooling system in the subject of the Maintenance of Light Vehicle in the XI Grade TKR SMKN 1 Palangka Raya academic year 2014/2015 is because the teacher delivers the material verbally without any variation. To overcome such problem, the application of learning model Take and Give is proposed. This research aims to understand the influence of learning model Take and Give on the study result of the students. Data were taken from two classroom. Classroom A (16 students) as the experiment group where the learning model will be applied, and Classroom B (16 students) as the control group where the verbal learning will be applied. Data collected from the post test result on the both group is tcalculated= 5,35 > ttable= 2,042 on the significancy level 5% dan df = (16+16-2) = 30.It can be seen that tcalculated ttable, thus Ho was rejected and HI was accepted so it can be concluded that there is an influence of learning model Take And Give on the student’s study result.